2010
DOI: 10.3109/00016481003769972
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception performance for 100 post-lingually deaf adults fitted with Neurelec cochlear implants: Comparison between Digisonic®Convex and Digisonic®SP devices after a 1-year follow-up

Abstract: Patients fitted with the Digisonic® SP implant showed significantly better scores after 3, 6, and 12 months (mean scores: 53%, 62%, and 68% for words; 58%, 69%, and 75% for sentences) than those fitted with the Convex implant (34%, 42%, and 43% for words; 38%, 59%, and 51% for sentences). The improvement in speech perception after implantation for SP patients continued throughout the 12 months for words and 6 months for sentences, versus 6 months for words and 3 months for sentences for Convex patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The large range of CI outcomes that we observed, as well as the mean performance, is consistent with previous reports from large-scale, international studies (13)(14)(15), indicating that the CI outcomes observed in the present study may be considered representative of the wider CI population.…”
Section: Resultssupporting
confidence: 80%
“…The large range of CI outcomes that we observed, as well as the mean performance, is consistent with previous reports from large-scale, international studies (13)(14)(15), indicating that the CI outcomes observed in the present study may be considered representative of the wider CI population.…”
Section: Resultssupporting
confidence: 80%
“…They reflect the usual interaural difference of which the etiological factors are still unknown [Mosnier et al, 2009;Basura et al, 2009]. Average speech performance of the best ear, in quiet, obtained with the Binaural device was not different from that obtained with the Digisonic SP in an unilateral implantation (62 vs. 68%, Mann-Whitney test, p = 0.42 [Lazard et al, 2010]). Therefore, even though 12 electrodes on each side are available instead of 20 in the unilateral Digisonic SP implant, these results are consistent with previous studies reporting that 10-12 electrodes are sufficient to provide good speech understanding in quiet [ Fu et al, 1998;Throckmorton et al, 1999;Friesen et al, 2001].…”
Section: Speech Performance In Quiet and In Noisementioning
confidence: 78%
“…Signal Processing and Stimulation Similar to the monaural Digisonic SP implant, the Digisonic SP Binaural implant uses the MPIS speech coding strategy (Main Peaks Interleaved Sampling, Di Lella et al [2009]; Lazard et al [2010]). This strategy combines peak extraction and sequential stimulation.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…Other sound processing has been added, such as ADRO (adaptive dynamic range optimization) that selects the most information-rich part of the signal and restores it to the optimal part of the listener's dynamic range [Blamey, 2005]. Other modifications in stimulation rates [Di Lella et al, 2010] or settings [James et al, 2003] have been implemented by each manufacturer, bringing improvements in outcomes [Firszt et al, 2009;Lazard et al, 2010a]. Such modifications, by easing central deciphering of CI stimulation of the auditory nerve, should result in better speech understanding in the whole of the CI population, with a shift of the distribution toward higher speech perception scores.…”
Section: Introductionmentioning
confidence: 99%